MENINGKATKAN HUBUNGAN SOSIAL ANTAR TEMAN SEBAYA MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK HOMEROOM DI SMK NEGERI 1 KUDUS - Rifki Nandito; Sucipto Sucipto; Agung Slamet Kusmanto (Universitas Muria Kudus, 2022)
Research Objectives: 1. Describe the action of Group guidance service with homeroom technique can improve social among peers of Class X SMK N 1 Kudus. 2. Improving social relationships between peers through Group guidance with Homeroom techniques for students X SMK N 1 Kudus. This study is a research action guidance counseling (PTBK). this research is from the application of Group guidance services with homeroom technique to improve the ability to establish social relationships, namely using qualitative and quantitative approaches. The approach used is qualitative and quantitative. In qualitative, the researcher seeks to give an idea of the increase in establishing friendship relationships in students ' social relationships described through descriptive words. While in quantitative, researchers collect data in the form of observation guidelines by comparing class averages, interviews, and documentation. The results of the study an increase in social relations between peers in students at SMK N 1 Kudus at each meeting that refers to each aspect